Agricultural labor, COVID-19, and potential implications for food security and air quality in the breadbasket of India. (November 2020) - Balwinder-Singh,; Shirsath, Paresh B.; Jat, M.L.; McDonald, A.J.; Srivastava, Amit K.; Craufurd, Peter; Rana, D.S.; Singh, A.K.; Chaudhari, S.K.; Sharma, P.C.; Singh, Rajbir; Jat, H.S.; et al.
Abstract: To contain the COVID-19 pandemic, India imposed a national lockdown at the end of March 2020, a decision that resulted in a massive reverse migration as many workers across economic sectors returned to their home regions. Migrants provide the foundations of the agricultural workforce in the 'breadbasket' states of Punjab and Haryana in Northwest India.There are mounting concerns that near and potentially longer-term reductions in labor availability may jeopardize agricultural production and consequently national food security. The timing of rice transplanting at the beginning of the summer monsoon season has a cascading influence on productivity of the entire rice-wheat cropping system. To assess the potential for COVID-related reductions in the agriculture workforce to disrupt production of the dominant rice-wheat cropping pattern in these states, we use a spatial ex ante modelling framework to evaluate four scenarios representing a range of plausible labor constraints on the timing of rice transplanting. Averaged over both states, results suggest that rice productivity losses under all delay scenarios would be low as compare to those for wheat, with total system productivity loss estimates ranging from 9%, to 21%, equivalent to economic losses of USD 674 m to 1.48 billion. Late rice transplanting and harvesting can also aggravate winter air pollution with concomitant health risks. Technological options such as direct seeded rice, staggered nursery transplanting, and crop diversification away from rice can help address these challenges but require new approaches to policy and incentives for change. Graphical abstract: Unlabelled Image Highlights: An ex-ante analysis was done using geospatial tools on potential effect of labour shortage on rice-wheat system. Food grain production loss due to labor shortage can be 23% from current levels of production. Residue burning will exacerbate air pollution in winter and could coincide with an anticipated COVID resurgence in the fall. India needs new strategies to use available technological and management innovations to address emerging constraints.